The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.51985/jbumdc2018067
|View full text |Cite
|
Sign up to set email alerts
|

Awareness Regarding Implant Supported Dental Prosthesis; A Survey In Tertiary Care Set Up

Abstract: Objective: This research was aimed to assess the awareness and attitude regarding implant-retained prosthesis as the most advanced option for tooth replacement amongst residents of Karachi visiting tertiary care centre. Methodology: This cross-sectional survey was conducted in the department of Prosthodontics at Bahria University Dental Hospital, Karachi. Undertaking the demographic characteristics of patients, the objective was to determine the awareness and attitude toward implant supported prosthesis. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Higher awareness of general health and prosthetic treatment options is perceived more by better-educated people. This is confirmed by the studies of Patil et al [12]; Saha et al [24]; Schützhold et al [25]; and Baqar et al [26]. Other researchers also observed that the de-sire to improve function and bite is the most important motivating factor for prosthetic treatment [13,27,28], and the results of this study and the study by Baqar et al [26] showed no gender difference.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Higher awareness of general health and prosthetic treatment options is perceived more by better-educated people. This is confirmed by the studies of Patil et al [12]; Saha et al [24]; Schützhold et al [25]; and Baqar et al [26]. Other researchers also observed that the de-sire to improve function and bite is the most important motivating factor for prosthetic treatment [13,27,28], and the results of this study and the study by Baqar et al [26] showed no gender difference.…”
Section: Discussionsupporting
confidence: 87%
“…This is confirmed by the studies of Patil et al [12]; Saha et al [24]; Schützhold et al [25]; and Baqar et al [26]. Other researchers also observed that the de-sire to improve function and bite is the most important motivating factor for prosthetic treatment [13,27,28], and the results of this study and the study by Baqar et al [26] showed no gender difference. In the study by Amjad and Aziz [29], 70.6% of men considered function as the most important reason for tooth replacement.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations